Triaxiality of High- K Isomers in A 130 Region - Liu Hong-Liang; Xu Fu-Rong (Chinese Physics Letters, 2008)
Remarkable triaxiality is found in the high-K isomeric states of A   130 nuclei using the configuration-constrained calculations of potential-energy surfaces. The triaxiality gives the further understanding of the decay properties of the isomers. The calculation with triaxiality can well explain the measured quadrupole moment of the K ¶– = 7 Å6”1 isomer in 130 Ce.